The Measurement Of Financial Reporting : Earnings Management and Firm Values - Sudaryo, Yoyo; Lenggogeni, Lenggogeni; Hakim NS, Dayan; Wardana, Wikrama; Permana, Omo; Lusiana Yulianti, Maria; Nur Sumawidjaja, Riyandi (Green Publisher, 2023)
In the span of 2014-2017, manufacturing firms situated in Indonesia's stock exchange were considered for analysis of the correlation between Earnings Management as an independent variable, Leverage, Profitability and Timeliness of Financial Reporting as a secondary dependent variable and Firm Value as a major dependent variable. The prime focus of the research was to formulate an understanding of how these variables impact the aforementioned businesses. The research questions were put to the test using Canonical Correlation Analysis as a method of data analysis. Through purposive sampling, organizations available were chosen. Over a span of 4 consecutive years, a total of 104 manufacturing companies were surveyed, sampled from 26 different establishments. In analyzing and testing the data, it was discovered that while the control variable leverage and profitability had an impact on firm value, the timeliness of financial reporting did not. However, the earnings management variables made a noteworthy impact.